3086 Virtual World-based Cardiac Rehabilitation to Promote Healthy Lifestyle Among Cardiac Patients. (27th March 2019) - Brewer, LaPrincess; Kaihoi, Brian; Leth, Shawn; Squires, Ray; Thomas, Randal; Scales, Robert; Trejo-Gutierrez, Jorge; Kopecky, Stephen
Abstract : OBJECTIVES/SPECIFIC AIMS: Our aim was to assess the feasibility and acceptability of a VW-based cardiac rehabilitation (CR) program (Destination Rehab) as an extension of a face-to-face conventional CR program. We hypothesized that a VW-based CR program could be successfully implemented as an extension of conventional CR and would have high acceptability among cardiac patients. METHODS/STUDY POPULATION: We recruited 30 adult cardiac patients (10/site) hospitalized at Mayo Clinic Hospitals in Rochester, MN, Jacksonville, FL or Scottsdale, AZ with a diagnosis for CR (eg, acute coronary syndrome (ACS), heart failure, elective percutaneous coronary intervention (PCI)). Other inclusion criteria included at least 1 modifiable, lifestyle risk factor target: sedentary lifestyle (< 3 hours physical activity (PA)/week), unhealthy diet (< 5 servings fruits and vegetables/day) or current smoking (>1 year). Patients participated in an 8-week, health education program using a VW platform from a prior proof-of-concept study and provided intervention usability, usefulness and satisfaction feedback. We assessed cardiovascular (CV) health behaviors (diet, PA) and risk factors (eg, blood pressure (BP), lipids) at baseline and immediate post-intervention. RESULTS/ANTICIPATED RESULTS: Among 30 patients enrolled (mean age; 59 years; 50% women; 65% <college graduate; 32% annual household income <50, 000), 28 (98%) completed the study. The majority (64%) were enrolled in conventional CR with a high session completion rate (median 36 sessions, interquartile range 8-36). The most common CR indication was PCI (68%). There were statistically significant improvements in PA from baseline to post-intervention: vigorous PA, +10.7 (SD 11.7) minutes/day (p = 0.05) and flexibility exercises +0.9 (SD 0.9) days/week for men (p=0.05). There were favorable trends in risk factors: systolic BP (−6.8 mmHg, SD 29.8), total cholesterol (−31.6 mg/dL, SD 46.2) and LDL (−26 mg/dL, SD 44.8) from baseline to post-intervention, although not statistically significant. The majority reported that they would continue to use VW as a resource (76%) and agreed/strongly agreed that the program improved their heart health knowledge (86%) and assisted with adapting healthier lifestyle (100%). Overall, the VW CR program received a rating of 8 (scale 0-10). DISCUSSION/SIGNIFICANCE OF IMPACT: VW-based CR program is a feasible, highly acceptable and innovative platform to influence health behaviors and CV risk and can increase accessibility to disadvantaged populations with higher CVD burdens.